Performance and Aging Characteristics of Hot Mixture Asphalt with Crumb Rubber and Warm Mix Asphalt Additives - Akpolat, Mustafa; Kok, Baha Vural; Yilmaz, Mehmet (Asce-Amer Soc Civil Engineers, 2020)
In this study, the mixes prepared using crumb rubber (CR) and binders with warm mix additives were aged through various aging methods (1, 2, 3, and 4 weeks at 60 degrees C in the laboratory; 2, 4, 6, 8, 10, and 12 months under the environmental conditions; and AASHTO R30) and examined in terms of performance and aging index. The indirect tensile strength (ITS), indirect tensile stiffness modulus (ITSM), and fatigue tests were applied to the pure and the CR,CR+Sasobit, andCR+Evothermmodified aged and nonaged mixes, and the aging indexes were determined according to the results obtained. According to the test results,CR+Sasobitwas found to be the best mix in terms of mechanical properties. Using the warm asphalt additives in the CR modification was determined to decrease the aging indexes and retarded the aging. Also determined was that a high correlation exists between the aging at 60 degrees C in the laboratory and the aging under the environmental conditions. Based on the fatigue test results, AASHTO R30 short-term aging (4 h at 135 degrees C) was determined to cause structural deterioration in the mixes and yielded low load repetition relative to the pure mixes. Therefore, using this method for the short-term aging of the CR modified mixes would not be appropriate. When the tests applied were evaluated in terms of the aging indexes, the fatigue test was found to be the most sensitive method for detecting aging in the pure mixes and mixes with additives. (C) 2020 American Society of Civil Engineers.
Keywords: Crumb rubber; Warm-mix additive; Aging; Aging index